Arabidopsis C‐terminal binding protein ANGUSTIFOLIA modulates transcriptional co‐regulation of MYB46 and WRKY33. Issue 5 (19th August 2020) - Xie, Meng; Zhang, Jin; Yao, Tao; Bryan, Anthony C.; Pu, Yunqiao; Labbé, Jessy; Pelletier, Dale A.; Engle, Nancy; Morrell‐Falvey, Jennifer L.; Schmutz, Jeremy; Ragauskas, Arthur J.; Tschaplinski, Timothy J.; et al.
Summary: The apparent antagonism between salicylic acid (SA) and jasmonic acid (JA)/ethylene (ET) signalling resulting in trade‐offs between defence against (hemi)biotrophic and necrotrophic pathogens has been widely described across multiple plant species. However, the underlying mechanism remains to be fully established. The molecular and cellular functions of ANGUSTIFOLIA (AN) were characterised, and its role in regulating the pathogenic response was studied in Arabidopsis. We demonstrated that AN, a plant homologue of mammalian C‐TERMINAL BINDING PROTEIN (CtBP), antagonistically regulates plant resistance to the hemibiotrophic pathogen Pseudomonas syringae and the necrotrophic pathogen Botrytis cinerea . Consistent with phenotypic observations, transcription of genes involved in SA and JA/ET pathways was antagonistically regulated by AN. By interacting with another nuclear protein TYROSYL‐DNA PHOSPHODIESTERASE1 (TDP1), AN imposes transcriptional repression on MYB46, encoding a transcriptional activator of PHENYLALANINE AMMONIA‐LYASE ( PAL ) genes which are required for SA biosynthesis, while releasing TDP1‐imposed transcriptional repression on WRKY33, a master regulator of the JA/ET signalling pathway. These findings demonstrate that transcriptional co‐regulation of MYB46 and WRKY33 by AN mediates the coordination of SA and JA/ET pathways to optimise defences against (hemi)biotrophic and necrotrophic pathogens.